Analisa Hukum Terhadap Tindak Pidana Ujaran Kebencian Melalui Media Sosial (Studi putusan No.370/Pid.Sus/2018/PNJKT.SEL) - Razali, Muhamad; Hartoyo, Hartoyo (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims in accordance with the title "Criminal Acts of Hate Speech Through Social Media (Study of decision No.370/Pid.Sus/2018/PNJKT." This research is normative legal research, namely legal research carried out by examining library materials or secondary data Also called doctrinal research, the discussion in this research is related to the elements of the criminal act of hate speech through social media, the judge's considerations in understanding the decision No. 370/Pid.Sus/2018/PNJKT.SEL the implementation of the sentence for the crime of hate speech in decision No. 370 The last /Pid.Sus/2018/PNJKT.SEL is closed by conclusions and suggestions.